Penerapan Genre Based Approach (GBA) dalam Pembelajaran Bahasa Inggris SMP - Luh Sri Narasintawati; Huraiyah Huraiyah; Sri Aliyah (Indonesian Publication Center, 2020)
As a language skill, English needs to be learned through clear steps through concept building, modelling, and practising processes. It is necessary, then, to find out an appropriate learning model capable of providing those steps. This paper aimed to reflect the teaching and learning process on the theme of Comparing Things and Animals by applying the Genre Based Approach with the Teaching-Learning Cycles (TLC) Model. This research was conducted at Class VIIIF SMP 14 Mataram, Lombok involving 28 students with 2 observers (a School Principal and an English Teacher). Data were collected using various techniques, such as observation and reflection, assignments and tests, focus group discussions (FGD), and documentation. The data were then analyzed descriptively. From the data analysis and learning reflection, it was concluded that (1) the application of GBA with the TLC Model provided students with gradual experiences of concept building, modelling, and practising both in groups and individually; (2) the application of GBA was also able to accommodate 4C elements in 21st Century Learning Skills; (3) there was an increase in the level of mastery learning from 32.14% with an average of 63.28 on the pre-test to 85.19% with an average of 79.67 on the post-test; (4) both observers provide a positive assessment of the learning process by applying GBA with TLC Model.